The philosophical content of the Avesto - Matnazarova Mukhayyo Axmetjanovna (International Journal on Orange Technologies, 2019)
This article affect public perceptions about the history of the Bible and the Qur'an, with legends like aspects , which affect the society at that time reflected in the legal and moral system. In the set of laws of Zoroastrianism, honesty, diligence, justice, objectivity in thought, word and deed are promoted as the basis of high moral norms